Baziyo: Development of a cryptogame with Unity on an Ethereum Blockchain Test Network - Silva, Eduardo Jorge Lira Antunes da; Araújo, Cristina Souza de; Silva Júnior, Jucimar Maia da; Gomes, Roberto Junio Rodrigues; Carvalho, Larissa Roque (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames), 2023)
The importance of developing software that keeps pace with Web3 technologies is crucial in fostering discussions about their utilization in the current scientific landscape. Within this context, this research aims to present the development of a "criptogame" that utilizes blockchain technology to incorporate NFTs (Non-Fungible Tokens) into its mechanics. The text addresses fundamental concepts of Web3, making references to relevant literature. Subsequently, the development process is described, including specific methodologies and models. The obtained results consist of a puzzle game that incorporates NFTs as playable characters and enables the transfer of these assets between digital wallets.